Subject selection: Adaptation of candid and street photography in Bandung City / Mohammad Firdaus Azman, Andang Iskandar and Yosa Fiandra - Azman, Mohammad Firdaus; Iskandar, Andang; Fiandra, Yosa (UiTM Perak Press, 2021)
First time stepping in Bandung is an unforgettable and spectacular adventure as it not only leads to academic collaboration but is also a decisive moment for the photographer. Upon arrival in Bandung, the camera lens has not stopped spinning and the photographer is bubbling with excitement to enjoy the splendid and breathtaking iconic tourist attractions of the country, which are vastly different from the landscapes in Malaysia. Due to limitation of time and equipment, and the environment beyond expectation, the photographer endeavours to challenge himself to get as much (subject matter) as he could in capturing candid and street portraits. When shooting around Bandung, practically everyone must work in a fast-paced environment (point & shoot images), as the photographer also needs to simplify his subject on the spot. The objective of article is simply to define content and analysis (subject matter), and expression of the artwork from the perspective of the artist. This study generally going to discuss based on the artwork (photograph) from the artists, especially in subject matter selection. The finding of this research justifies that with this kind of theme (candid and street photo) we as photographers can employ our tools and techniques to compose almost anything into a strong photography subject, according to our own perspective. In conclusion, shooting photographs in Bandung City is quite a fantastic experience which will always be remembered, yet it is suggested that we always need to keep in mind the elements of composition the technique, your vision, and your imagination, that will best help you communicate what you are trying to express in the photograph.